An integrated DNA and RNA variant detector identifies a highly conserved three base exon in the MAP4K5 kinase locus. Issue 12 (2nd December 2021) - Kurkowiak, Małgorzata; Grasso, Giuseppa; Faktor, Jakub; Scheiblecker, Lisa; Winniczuk, Małgorzata; Mayordomo, Marcos Yebenes; O'Neill, J. Robert; Oster, Bodil; Vojtesek, Borek; Al-Saadi, Ali; Marek-Trzonkowska, Natalia; Hupp, Ted R.
ABSTRACT: RNA variants that emerge from editing and alternative splicing form important regulatory stages in protein signalling. In this report, we apply an integrated DNA and RNA variant detection workbench to define the range of RNA variants that deviate from the reference genome in a human melanoma cell model. The RNA variants can be grouped into (i) classic ADAR-like or APOBEC-like RNA editing events and (ii) multiple-nucleotide variants (MNVs) including three and six base pair in-frame non-canonical unmapped exons. We focus on validating representative genes of these classes. First, clustered non-synonymous RNA edits (A-I) in the CDK13 gene were validated by Sanger sequencing to confirm the integrity of the RNA variant detection workbench. Second, a highly conserved RNA variant in the MAP4K5 gene was detected that results most likely from the splicing of a non-canonical three-base exon. The two RNA variants produced from the MAP4K5 locus deviate from the genomic reference sequence and produce V569E or V569del isoform variants. Low doses of splicing inhibitors demonstrated that the MAP4K5-V569E variant emerges from an SF3B1-dependent splicing event. Mass spectrometry of the recombinant SBP-tagged MAP4K5 V569E and MAP4K5 V569del proteins pull-downs in transfected cell systems was used to identify the protein-protein interactions of these two MAP4K5 isoforms and propose possible functions. Together these data highlight the utility of this integrated DNA and RNA variant detection platform to detect RNA variants in cancer cells and support future analysis of RNA variant detection in cancer tissue.